Guillain-Barre Syndrome: A Retrospective Study of Clinical and Epidemiological Features in Kurdistan, West of Iran, From 2005 To 2014 - Payam Khomand; Sajjad Abdolmaleki; Ebrahim Ghaderi; Sahar Khoshravesh (Shahrekord University of Medical Sciences, 2018)
Background and aims: The most common cause of acute flaccid paralysis of all ages is Guillain-Barre syndrome (GBS). Further understanding of this disease is important because of its life-threatening nature in life. The aim of this study was to conduct a 10-year survey on epidemiological and clinical features of GBS in Tohid and Besat hospitals, Sanandaj, Iran, from 2005 to 2014. Methods: This study was a retrospective study, based on medical records, in which 98 hospitalized cases in Tohid and Besat hospitals (tertiary referral hospitals), Sanandaj, Iran, between 2005 and 2014 were investigated. The epidemiological and clinical information was obtained from eligible cases. Data analysis was performed using SPSS version 16. Chi-square and t test were used for analyses. The significant level was considered at P<0.05. Results: The mean age of cases with GBS was 22.16 years. Among final 69 patients who were studied, 36 cases (52.2%) were male and 33 cases (47.8%) were female. Most cases of disease occurred in the spring. Thirty-nine patients (56.52%) had risk factors like history of gastrointestinal infections, respiratory infections, and surgery 2-4 weeks before the disease onset. Four cases (10.25%) needed mechanical ventilation. The most common protocol of treatment was IVIg (n=47, 68%). More than half of the patients (52.2%) achieved relative recovery. In 6 patients, (8.7%) relapse was occurred. Conclusion: Our study showed that there was a significant relationship between sensory- motor involvement, gender and age. Moreover, the relationship between gender and prognosis was indicated (P<0.05).